Pain sensitivity and plasma beta-endorphin in adolescent non-suicidal self-injury - Venne, Patrice van der; Balint, Andrea; Flach, Elisa; Parzer, Peter; Resch, Franz; Koenig, Julian; Kaess, Michael (Journal of affective disorders, 2021)
Background - Beta-endorphin (BE) has been suggested to play a central role as to why people engage in NSSI. To our knowledge, no study has systematically assessed this potential relationship in adolescents with NSSI. - Methods - 94 adolescents with NSSI (according to DSM-5 criteria) and 35 healthy controls (HC) were enrolled. All participants received heat pain stimulation, with pain threshold and tolerance measured in °C. Plasma BE levels were assessed. Sociodemographic and clinical characteristics were obtained via semi-structured interviews and self-report questionnaires. - Results - Adolescents with NSSI showed increased pain thresholds (t(127)=2.071, p=.040), lower pain intensity (t(114)==2.122, p=.036) and lower plasma BE levels (t127==3.182, p=.002) compared to HC. Groups did not differ on pain tolerance (t(127)=0.911, p=.364). Greater pain threshold correlated positively with borderline personality disorder (BPD) symptoms (r=0.182, p=.039), while pain intensity (r=-0.206, p=.033) and BE levels (r=-0.246, p=.007) correlated negatively with depression severity. No significant relationship was found between pain threshold and plasma BE (r=-0.013, p=.882). - Limitations - Future studies should implement repeated plasma BE measures to assess BE release in association with pain in NSSI. Validity of plasma BE measures compared to central measures should be considered. Assessing the association between pain sensitivity (PS) and BE in a naturalistic setting presents a promising avenue for future research in NSSI. - Conclusions - Findings support both reduced PS and basal opioid deficiency as independent biological correlates and potential risk-factors for NSSI. Further longitudinal and experimental studies are needed to investigate the role of BE levels and PS as well as their potential association.
Available online 11 September 2020
Gesehen am 30.03.2021